A Comparison of Different Joining Options of Hybrid Composite Joints for Improved Fatigue Life - Khawaja, A. H.; Tariq, A.; Khan, W. A.; Baig, Y. (The Nucleus, 2016)
The use of composite materials has increased rapidly in the last couple of decades especially in the aerospace industry due to its lighter weight, higher stiffness and better fatigue properties. The fiber metal laminates (FML) assemblies design normally involves an interaction between composites (carbon fiber) and metallic parts (AA 6061 T6) and these interfaces often prove to be the weakest portions of the structures. This research has therefore focused on carrying out a comparison of different joining techniques of composites with metals keeping in view the tensile and fatigue properties of double lap joint configuration. For this purpose simple adhesive joints, hybrid joints (adhesive +rivets) and joints having adhesive pins in metal plate were prepared and tested. The research also involves finite element modeling of these joints and their subsequent experimental validation. The results showed higher strength of hybrid joint, in which a combination of fasteners and adhesive was used; however, the novel idea of using adhesive pins could not be successful.